Antimicrobial effect of acidified nitrite on gut pathogens: importance of dietary nitrate in host defense. - Dykhuizen, R S (1996)
Dietary intake of nitrate generates salivary nitrite, which is acidified in the stomach, leading to a number of reactive intermediates of nitrogen, among which are the potentially carcinogenic N-nitrosamines. Acidified nitrite, however, also has antimicrobial activity which coincides with the formation of nitric oxide. The present study examines the antimicrobial effect in vitro of acidified nitrite on Salmonella enteritidis, Salmonella typhimurium, Yersinia enterocolitica, Shigella sonnei, and Escherichia coli O157. First-order regression plots showed a linear inverse relationship of log-transformed proton and nitrite concentrations with MICs and MBCs after 30 min, 2 h, and 24 h of exposure (P < 0.001 for all antibacterial activities). Susceptibility to the acidified nitrate solutions ranked as follows: Y. enterocolitica > S. enteritidis > S. typhimurium = Shigella sonnei > E. coli O157 (P < 0.05). Addition of SCN-, but not that of CI-, increased the antibacterial activity (paired t testing, P < 0.001). Generation of salivary nitrite from dietary nitrate may provide significant protection against gut pathogens in humans.